The Role of Islamic Religious Education Teachers in Improving Character Integrity through In-Depth Learning at Dharma Karya Vocational School, Jakarta - Arradhin, Aniisah Azka; Rahmanto, Muhammad Arifin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study examines the role of islamic religious education (PAI) teachers in enhancing students character integrity through in depth learning at smk dharma karya jakarta.using qualitative descriptive methods,data were collected through observation,interviews,and documentation.the results indicate that pai teachers act as moral guides and reflection facilitators,linking islamic values to students real lives.through reflective discussions,learning projects,and authentic assesments,teachers are able to fostur the values of honesty,responsibility,and discipline in a more in depth manner.in depth learning has proven effective in strengthening students character integrity.